2018
DOI: 10.1021/acs.est.8b01888
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reactive Ultrafiltration Membrane for Removal of Antibiotic Resistant Bacteria and Antibiotic Resistance Genes from Wastewater Effluent

Abstract: Biological wastewater treatment is not effective in removal of antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs). In this study, we fabricated a photocatalytic reactive membrane by functionalizing polyvinylidene fluoride (PVDF) ultrafiltration (UF) membrane with titanium oxide (TiO) nanoparticles for the removal of ARB and ARGs from a secondary wastewater effluent. The TiO-modified PVDF membrane provided complete retention of ARB and effective photocatalytic degradation of ARGs and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(62 citation statements)
references
References 50 publications
(81 reference statements)
2
60
0
Order By: Relevance
“…Jiang et al (2016) reported the fully inactivated antibiotic-resistance bacterium blaTEM-1 and aac(3)-II antibiotic-resistance genes via photoelectrocatalytic process, using semiconductor TiO 2 nanotubes [138]. Ren et al (2018) reported removing ARB and ARGs from a secondary wastewater effluent using a photocatalytic reactive membrane, using a polyvinylidene fluoride ultrafiltration membrane functionalized with nanoparticles of TiO 2 . The degradation efficiencies of the hybrid method were 97.82%, 20.66%, 99.45%, and 93.67% for floR, tetC, sul1, and intI1 in the plasmid [140].…”
Section: Advanced Oxidation Processesmentioning
confidence: 99%
“…Jiang et al (2016) reported the fully inactivated antibiotic-resistance bacterium blaTEM-1 and aac(3)-II antibiotic-resistance genes via photoelectrocatalytic process, using semiconductor TiO 2 nanotubes [138]. Ren et al (2018) reported removing ARB and ARGs from a secondary wastewater effluent using a photocatalytic reactive membrane, using a polyvinylidene fluoride ultrafiltration membrane functionalized with nanoparticles of TiO 2 . The degradation efficiencies of the hybrid method were 97.82%, 20.66%, 99.45%, and 93.67% for floR, tetC, sul1, and intI1 in the plasmid [140].…”
Section: Advanced Oxidation Processesmentioning
confidence: 99%
“…The synergistic effect of the hydrophilic and charged functional groups of GO-PEI contributed to the formation of dense hydration layer on the membrane surface, thereby reducing membrane fouling. Ren, Boo, et al (2018) fabricated a photocatalytic reactive membrane by functionalizing the PVDF UF membrane with titanium oxide (TiO 2 ) NP for removal of antibiotic-resistant bacteria (ARB) and antibiotic-resistant genes (ARGs) from secondary wastewater effluent. The researchers reported the TiO 2 -modified PVDF membrane provided complete removal of ARB and effective photocatalytic degradation of ARGs and integrons.…”
Section: Development Of New Membranesmentioning
confidence: 99%
“…Recently, efforts have been made to develop a new class of hybrid material which can not only use for detecting air pollution but also for monitoring water pollution. The degradation of organic pollutants and the inactivation of pathogenic bacteria in waste water are two of the most important issues for environmental remediation …”
Section: Figurementioning
confidence: 99%